PLGA nanoparticles containing praziquantel: effect of formulation variables on size distribution - Mainardes, R. M.; Evangelista, R. C. (Elsevier B.V., 2005)
Praziquantel has been shown to be highly effective against all known species of Schistosoma infecting humans. Spherical nanoparticulate drug carriers made of poly(D,L-lactide-co-glycolide) acid with controlled size were designed. Praziquantel, a hydrophobic molecule, was entrapped into the nanoparticles with theoretical loading varying from 10 to 30% (w/w). This investigates the effects of some process variables on the size distribution of nanoparticles prepared by emulsion-solvent evaporation method. The results show that sonication time, PLGA and drug amounts, PVA concentration, ratio between aqueous and organic phases, and the method of solvent evaporation have a significant influence on size distribution of the nanoparticles. (C) 2004 Elsevier B.V. All rights reserved.
Keywords: nanoparticles; controlled release; PLGA; praziquantel; emulsification evaporation method